Characterization of Brucella infection in ruminant hosts: disease pathogenesis, immunology, and epidemiology - Higgins, Jennifer, author; Bowen, Richard A., advisor; Gonzalez-Juarrero, Mercedes, advisor; Nol, Pauline, committee member; Callan, Robert J., committee member (Colorado State University. Libraries, 2015)
Brucellosis is one of the most common zoonotic diseases worldwide, with endemic disease areas in the Middle East, Mediterranean Basin, Central Asia, Africa, and Central and South America. Disease is caused by various species of the gram negative bacteria Brucella. Infection in humans results primarily from contact with infected livestock or consumption of contaminated livestock products; cattle, small ruminants, and swine are the primary reservoir hosts. Although the Brucella bacterium was discovered over a century ago, control of disease remains a major challenge in many areas worldwide. Research on this pathogen has mostly been conducted in mouse models, which are naturally resistant to infection. Little is known of the immune response of natural ruminant hosts to Brucella infection. Here we report an epidemiological study of brucellosis in Mongolia, as well as an experimental infection study of pregnant goats with two strains of B. melitensis – 16M, a fully virulent strain, and Rev. 1, a reduced virulence vaccine strain. Design of the experimental infection study was influenced by findings from field research in an endemic disease region. The objectives of the experimental challenge study were to characterize clinical disease, shedding, and tissue burdens in infected animals. The cellular immune response was then compared in animals infected with the two B. melitensis strains with the aim of identifying components of the protective response induced by the Rev. 1 vaccine strain and deficits in the immune response elicited by infection with virulent B. melitensis 16M. A fluorescence polarization assay was utilized to identify antibodies in milk samples and estimate the proportion of Brucella positive cattle, yak, and hybrids in three regions of Mongolia. Additionally, prevalence of brucellosis in herd owners was assessed via questionnaire. Information was also collected from herd owners regarding animal husbandry practices and herd health in order to identify individual-and herd-level characteristics that are predictive for brucellosis. The study indicates that brucellosis remains endemic in cattle, yak, and hybrids within Bulgan and Khuvsgul provinces of Mongolia despite a national control program. Herd level prevalence was determined to be 10.4% in the 77 herds tested. High levels of human disease were also reported. Results of the study indicate that the Mongolian brucellosis control program must be critically evaluated if the national goal of obtaining brucellosis-free status by 2021 is to be realized. In an experimental challenge study, pregnant does infected with B. melitensis 16M at midgestation had an 86% abortion rate, while no Rev. 1-infected does aborted. Fetal infection rate was 92% and 43% in kids of 16M- and Rev. 1-infected does, respectively. Widespread tissue colonization was noted in 100% of 16M-infected does, and all of these animals shed brucellae in milk and vaginal secretions. Infection in does inoculated with Rev. 1 was more variable with only one animal showing generalized infection and colonization at levels similar to that of 16M-infected animals. Other Rev. 1-innoculated animals showed low levels of focal infection and shedding. Here we report the first isolation of B. melitensis from muscle tissue of experimentally infected goats. Milk was also found to pose a significant public health risk with three 16M-infected animals consistently shedding brucellae at levels of 104 – 107 CFU/ml over the four days on which samples were collected postpartum. Despite the clear differences in clinical disease resulting from infection with the two strains of B. melitensis, protective versus deficient components of the immune response elicited by these two strains remain undefined. A pro-inflammatory response characterized by increases in granulocytes, monocytes, and CD4+ lymphocytes was identified by flow cytometric analysis of blood from 16M-infected does. In comparison cell numbers remained consistent with pre-infection levels in Rev. 1-inoculated animals. Limited production of IFN-γ and low level expression of the CD25 activation marker indicate a potential anergic state of CD4+ T cells in B. melitensis-infected goats. Increased numbers of IFN-γ producing WC1+ gamma-delta T cells at 28 days post-infection in Rev. 1-inoculated goats in comparison to 16M-infected animals may suggest a role of this cell type in the protective response elicited by the Rev. 1 vaccine strain. The research presented in this dissertation builds upon current knowledge of Brucella epidemiology, pathogenesis, and immunology in natural ruminant hosts. The work provides a strong framework from which further comparative investigations of immune response to virulent B. melitensis and the reduced virulence B. melitensis vaccine strain, Rev. 1, can be conducted with the ultimate goal of defining components of a protective versus deficient response to Brucella in a natural host. This will ultimately aid in development of improved vaccines facilitating control of disease in endemic areas like Mongolia.
Keywords: brucellosis; caprine; goat; Mongolia; ruminant; Brucella